Love the Sin : Sexual Regulation and the Limits of Religious Tolerance. - Jakobsen, Janet R. (Sexual cultures., 2003)
Sex. Religion. There is no denying that these two subjects are among the most provocative in American public life. Even the constitutional principle of church-state separation seems to give way when it comes to sex: the Supreme Court draws on theology as readily as it draws on case law when rendering decisions that touch on sexuality. In this compelling and carefully argued study, Janet R. Jakobsen and Ann Pellegrini examine this powerful and disturbing connection as they explore the reasons why secular institutions habitually use religion to regulate sexual life. From state legislatures to th.